Struktura semantyczna pojęć „wolność sumienia i religii”, „wolność sumienia i wyznania” (część I) - Hordecki, Bartosz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
The aim of this paper is to present a general semantic structure of the notions of the “freedom of conscience and religion” and “freedom of conscience and religious denomination.” The text refers to the concept of Ch. L. Stevenson, by means of a differentiation between the descriptive and emotive levels of the notions. The descriptive and emotive senses of both notions are presented vis-à-vis the evolution of the notions of “dignity” and “tolerance”. The persuasive and manipulative potential contained in the notions of the “freedom of conscience and religion” and “freedom of conscience and religious denomination” is also emphasized.